A qualitative examination of the usability of a digital cognitive behavioral therapy for insomnia program after stroke. (28th January 2022) - Smejka, Tom; Henry, Alasdair L; Wheatley, Catherine; Espie, Colin A; Johansen-Berg, Heidi; Fleming, Melanie K
ABSTRACT: Objective: Sleep is commonly impaired after stroke. Cognitive Behavioral Therapy for Insomnia (CBT-I) is the first-line recommended treatment for sleep difficulty. "Sleepio" is a digital CBT-I program, allowing delivery of this treatment at scale. However, Sleepio has not yet been tested specifically in people with stroke. Before doing so, we wanted to explore the experience of people with stroke using the program, and potential barriers to completion. Method: Community dwelling survivors of stroke (n = 11, 41–78 years of age, 6 male) were given access to Sleepio. Participants discussed their experiences with the program during a semi-structured interview, which was analyzed using thematic analysis. Results: We found four common themes: (1) positive and negative experiences impacted engagement with the program, (2) motivation to follow the program was proportional to perceived severity of sleep problem, (3) impractical advice for people with stroke, (4) difficulty operating the program. Conclusion: Sleepio can be used by some people at the chronic stage of stroke. However, some barriers to completion were highlighted, and not all suggestions were deemed practical for everyone. We therefore suggest possible adaptations which may make the program more easily usable and engaging for survivors of stroke with varying impairments.